Why do flowers in Namaqualand close? : Flower closure in relation to the environment and pollen sensitivity to moisture - Von Hase, Amrei (Department of Biological Sciences, 2017)
Namaqualand, South Africa, is a desert system characterised by predictable winter rainfall and mild temperatures. Flowering coincides with the wet season which imposes constraints on pollination success. The wide-spread phenomenon of flower closure in the flora may represent an adaptation for protecting sensitive pollen from damage by moisture (dew, rain). The literature dealing with the subject is sparse and we addressed this gap by investigating patterns of flower closure in relation with environmental variables (potential cues). We also determined the effect of water on pollen in field and laboratory situations. The findings are that air temperature closely reflects moisture levels and is the cue for diurnal patterns in flower closure. Of the abiotic factors tested, it best explains the biological variable of flower temperature which is closely correlated with flower closure. Variation among species in their response to ambient temperature is demonstrated by individual thresholds for flower opening and differing strengths of the relationship. The detrimental effect of moisture on pollen viability emerges in four species (Mesembryanthemaceae, Asteraceae) where exposure to water caused significant pollen damage. Field experiments on two of these species confirm significant damage under natural conditions. Petal closure is the dominant protective mechanism in these plants and effectively prevents losses in reproductive potential caused by moisture. This has evolutionary significance as many Namaqualand species persist via annual recruitment. In two species (Asteraceae) that do not close their petals above inflorescences, pollen viability was retained despite placement in water. They may have a different protective strategy, such as a germination inhibitor, or their pollen could be insensitive to water.